Stomach position in prediction of survival in left‐sided congenital diaphragmatic hernia with or without fetoscopic endoluminal tracheal occlusion. (August 2015) - Cordier, A.‐G.; Jani, J. C.; Cannie, M. M.; Rodó, C.; Fabietti, I.; Persico, N.; Saada, J.; Carreras, E.; Senat, M.‐V.; Benachi, A.
Abstract Objective To investigate the value of fetal stomach position in predicting postnatal outcome in left‐sided congenital diaphragmatic hernia (CDH) with and without fetoscopic endoluminal tracheal occlusion (FETO). Methods This was a retrospective review of CDH cases that were expectantly managed or treated with FETO, assessed from May 2008 to October 2013, in which we graded, on a scale of 1–4, stomach position on the four‐chamber view of the heart with respect to thoracic structures. Logistic regression analysis was used to investigate the effect of management center (Paris, Brussels, Barcelona, Milan), stomach grading, observed‐to‐expected lung area‐to‐head circumference ratio (O/E‐LHR), gestational age at delivery, birth weight in expectantly managed CDH, gestational ages at FETO and at removal and period of tracheal occlusion, on postnatal survival in CDH cases treated with FETO. Results We identified 67 expectantly managed CDH cases and 47 CDH cases that were treated with FETO. In expectantly managed CDH, stomach position and O/E‐LHR predicted postnatal survival independently. In CDH treated with FETO, stomach position and gestational age at delivery predicted postnatal survival independently. Conclusion In left‐sided CDH with or without FETO, stomach position is predictive of postnatal survival. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.